Au@h-Al2O3 analogic yolk–shell nanocatalyst for highly selective synthesis of biomass-derived d-xylonic acid via regulation of structure effects. Issue 22 (23rd October 2018) - Ma, Jiliang; Liu, Zewei; Song, Junlong; Zhong, Linxin; Xiao, Dequan; Xi, Hongxia; Li, Xuehui; Sun, Runcang; Peng, Xinwen
Abstract : Au@ h -Al2 O3 analogic yolk–shell nanocatalyst for highly selective synthesis of biomass-derivedd -xylonic acid via regulation of structure effects. Abstract : Selective oxidation of biomass-based monosaccharides into value-added sugar acids is highly desired, but limited success of producingd -xylonic acid has been achieved. Herein, we report an efficient catalyst system, viz ., Au nanoparticles anchored on the inner walls of hollow Al2 O3 nanospheres (Au@ h -Al2 O3 ), which could catalyze the selective oxidation ofd -xylose intod -xylonic acid under base-free conditions. The mesoporous Al2 O3 shell as the adsorbent first adsorbedd -xylose. Then, the interface of Au nanoparticles and Al2 O3 as active sites spontaneously dissociated O2, and the exposed Au nanoparticle surface as the catalytic site drove the transformation. With this catalyst system, the valuabled -xylonic acid was produced with excellent yields in the aerobic oxidation ofd -xylose. Extensive investigation showed that Au@ h -Al2 O3 is an efficient catalyst with high stability and recyclability.